SIHO: SPIRITUAL SYMBOL IN KHON KAEN CITY - Bamrungphak, Sowit (ASEAN Journal of Religious and Cultural Research, 2018)
‘Siho’ or ‘Thow Si ho’ in Synshai which is Buddhist literature, the son of Phraya Kusaraj, the governor of Peng Chang City and his wife, Chantha. He was born with two younger brothers, Synshai and Hoi-Sang. Synshai, ‘Siha-cakkra-raja’ is a name set by Indra. Siho looks like a lion with elegant shape and its main features are: purely clean animal and elephant shape with an elephant head, a lion body and a horse tail. This leads to the interpretation that the ‘trunk’ is the organ for food and drink. It's like having a far vision in development, bringing prosperity to Khon Kaen City. ‘Ivory’ is a symbol of worthiness, like Khon Kaen, which is a beautiful city with precious traditions, religions and culture to be promoted. ‘A large ear’ represents Khon Kaen Municipality administrators that must listen to and heal the suffering of the Khon Kaen people. The ‘head’, in the ancient time, it was believed that elephants must have a large head as a knowledge center (brain stores), refers to the good, effective and various educations that have been developed in Khon Kaen. The ‘feet’ are clawed, clinging to the ground and standing pompously; it is like Khon Kaen people that have a strong base of life and ‘a tail’ to fend off insects, like the Khon Kaen people will be protected and will be so happy infinity.